2002
DOI: 10.1002/jms.316
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phenylbutyrylglutamine, a new metabolite of phenylbutyrate metabolism in humans

Abstract: Phenylbutyrate is used in humans for treating inborn errors of ureagenesis, certain forms of cancer, cystic fibrosis and thalassemia. The known metabolism of phenylbutyrate leads to phenylacetylglutamine, which is excreted in urine. We have identified phenylbutyrylglutamine as a new metabolite of phenylbutyrate in human plasma and urine. We describe the synthesis of phenylbutyrylglutamine and its assay by gas chromatography/mass spectrometry as a tert-butyldimethylsilyl or methyl derivative, using standards of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
(33 reference statements)
1
18
1
Order By: Relevance
“…PBGN is presumably formed from the reaction of PB-CoA with glutamine, by analogy with the formation of PAGN from the reaction between PA-CoA and glutamine (Webster et al, 1976). In normal adult sub-jects who ingested a fairly low dose of PB (5 g/75 kg), we found that the total excretion of PB ϩ PA ϩ PAGN ϩ PBGN accounted for only half the ingested PB dose (Comte et al, 2002). The missing fraction of the dose may be disposed of either in urine as unknown metabolites, or in feces as unabsorbed PB and/or PB metabolites.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…PBGN is presumably formed from the reaction of PB-CoA with glutamine, by analogy with the formation of PAGN from the reaction between PA-CoA and glutamine (Webster et al, 1976). In normal adult sub-jects who ingested a fairly low dose of PB (5 g/75 kg), we found that the total excretion of PB ϩ PA ϩ PAGN ϩ PBGN accounted for only half the ingested PB dose (Comte et al, 2002). The missing fraction of the dose may be disposed of either in urine as unknown metabolites, or in feces as unabsorbed PB and/or PB metabolites.…”
mentioning
confidence: 84%
“…[ 2 H 5 ]PB was prepared by aluminum chloride-catalyzed condensation of ␥-butyrolactone with [ 2 H 6 ]benzene as previously described (Comte et al, 2002). ␥-Phenyl-trans-crotonic acid was prepared by a Fridel-Crafts reaction of benzene with ethyl ␥-bromo-trans-crotonate, followed by acid hydrolysis of ethyl ␥-phenyl-trans-crotonate (Loffler et al, 1970 2 H]propanol is outlined in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alanine Arachidonoyl [76] γ-Aminobutyric acid Arachidonoyl [76] Glutamic Acid β-Citryl and phenylacetyl [54,55,114] Glutamine Phenylacetyl, other arylacetyls, and 4-phenylbutyryl [55,114] Glycine c Arachidonoyl, benzoyl, butyryl, bile acids, decanoyl, hexanoyl, isobutyryl, 2-methylbutyryl, 3-methylcrotonyl, octanoyl, phenylacetyl and other arylacetyls, propionyl, suberyl, and tiglyl [7,55,57,65,76,84,115] Isoleucine Lactyl [116] Leucine Lactyl [116] Phenylalanine Succinoyl [117] Pyroglutamic acid Phenylacetyl [57] Serine Arachidonoyl [71] Taurine Bile acids, phenylacetyl and other arylacetyls, long chain, saturaturated acyl groups from C16:0-C26:0 d , long-chain, monounsaturated acyl groups from C18:1-C24:1 d [7,84,118] Valine Lactyl [116] a N-Acetyl and N-isovaleroylamino acids were not included in this table.…”
Section: Amino Acid B N-acyl Group Referencesmentioning
confidence: 99%